-9=2v+9-5v+6

Simple and best practice solution for -9=2v+9-5v+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9=2v+9-5v+6 equation:


Simplifying
-9 = 2v + 9 + -5v + 6

Reorder the terms:
-9 = 9 + 6 + 2v + -5v

Combine like terms: 9 + 6 = 15
-9 = 15 + 2v + -5v

Combine like terms: 2v + -5v = -3v
-9 = 15 + -3v

Solving
-9 = 15 + -3v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '3v' to each side of the equation.
-9 + 3v = 15 + -3v + 3v

Combine like terms: -3v + 3v = 0
-9 + 3v = 15 + 0
-9 + 3v = 15

Add '9' to each side of the equation.
-9 + 9 + 3v = 15 + 9

Combine like terms: -9 + 9 = 0
0 + 3v = 15 + 9
3v = 15 + 9

Combine like terms: 15 + 9 = 24
3v = 24

Divide each side by '3'.
v = 8

Simplifying
v = 8

See similar equations:

| 1440=(x-2)*180 | | J=7t+-3t | | 4(x-7)-10=2 | | 2cos(x)+1=0.5 | | 5x^2+28x+-12=0 | | 6+6x=-60 | | 1.25g=15g+.50 | | y=2(1)+2.50(1) | | -4+7x=-46 | | 4+8=8+x | | 12x^2+-8x+1=0 | | n+6.92=11.77 | | -7-3x=29 | | 14.75g=.50 | | (2x+10)(3x-1)=150 | | 3p+45=68 | | 1.5-2= | | (5w-1)(5+w)=0 | | (2x-3)+1=17 | | 3.5+-9= | | -3(1-4n)=-63 | | y=2*4+2.50*4 | | (7+4w)=13 | | -26+7p=5(3p+6) | | -3(1-4n)=63 | | -3(1-4)=-63 | | 1.5-7= | | y=2(2)+2.50(2) | | 3b+-4=14 | | -15a-a+4=64 | | -21n-15=-82 | | -13a-18=73 |

Equations solver categories